Item-method directed forgetting and working memory capacity: a hierarchical multinomial modeling approach - Marevic, Ivan; Arnold, Nina Rebecca; Rummel, Jan (Quarterly journal of experimental psychology, 2018)
Intentional forgetting of information that has recently been encoded is regarded an active and adaptive process and is widely studied using the item-method or the list-method directed forgetting (DF) paradigm. In the present research, we tested whether inter-individual differences in working-memory capacity (WMC), that have been identified as a relevant predictor of DF within the list-method, are also related to stronger DF effects within the item-method. Furthermore, we investigated relationships between WMC and item-method DF at different processing stages by applying the multinomial storage-retrieval model (Riefer & Rouder, 1992) hierarchically to our data. Results showed that individuals with high WMC are better able to store to-be-remembered information than individuals with low WMC; whereas WMC was not related to retrieval of to-be-remembered information or to either storage or retrieval of to-be-forgotten information. Implications for theoretical accounts of item-method DF are discussed.